A new syntopic species of small barb from the Western Ghats of India (Teleostei: Cyprinidae) - Katwate, Unmesh; Kumkar, Pradeep; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2018)
A new species of the cyprinid genus Pethia is described from the Hiranyakeshi, a tributary of the Krishna River system in the Western Ghats mountain ranges of peninsular India. The new species, Pethia sahit, is syntopic—and shoals together—with Pethia longicauda, a species described recently from the same river. Pethia sahit is distinguished from P. longicauda and its congeners by a combination of characters like, incomplete lateral line with 3–6 pored scales; 19–22 scales in lateral series; 4½ scales between dorsal-fin origin and lateral-line row and 2½ scales between lateral line row and pelvic-fin origin; intercalated scale row originates above and after the 6th scale of the lateral-line scale row; dorsal fin originating behind the pelvic-fin origin; 4+13 abdominal and 12 caudal vertebrae; dorsal, pectoral, pelvic, anal and caudal fins without any bands or spots, deep yellow-orange in color or deep red with a pale tint of orange in mature males; a dark-black vertically elongate humeral spot, overlapping the 4th lateral-line scale, extending over the base of one scale above and below the 4th scale; caudal peduncle spot dark, covering 14th–16th scales in lateral-line scale row. Genetic analysis based on the mitochondrial cytochrome b gene indicates that P. sahit and P. longicauda are not sister taxa. Further, P. sahit has no genetically proximate congener in the Western Ghats region, and differs from known congeners from south and southeast Asia, for which genetic data are available, with genetic distance ranging from 11.8–16.4%.